Compact Microstrip Lowpass Filter with Wide Stopband and Sharp Roll-off using Triple Radial Stubs Resonator - Hayati, M.; Memari, H. AL.; Abbasi, H. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel microstrip lowpass filter with good specifications such as sharp cutoff, wide stopband, low insertion loss, and high return loss is proposed. The proposed lowpass filter is realized using triple radial stubs resonator, i.e., three 60o radial stubs and harmonic attenuator, i.e., T shaped cell loaded by the semicircle. The cutoff frequency of the proposed filter is adjusted to 1.39 GHz. The transition band is approximately 0.21 GHZ from 1.39 GHz to 1.6 GHz with corresponding attenuation levels of -3 dB and -20 dB. The stopband with better than -20 dB rejection is from 1.6 GHz to 12.36 GHz, insertion loss in the passband is less than 0.1 dB, return loss is less than -25 dB and the overall size of the filter is 0.0074 ?g2 ( 15 × 12.3 mm2 ). The proposed filter is fabricated and measured. The simulation and measurement results are in good agreement.